2004
DOI: 10.1029/2004eo350001
|View full text |Cite
|
Sign up to set email alerts
|

Seismic, acoustic, and thermal network monitors the 2003 eruption of Stromboli Volcano

Abstract: The date 28 December 2002, heralded the onset of a 7‐month‐long effusive eruption at Stromboli volcano in Italy. The onset was accompanied on 30 December by a large landslide (Figure 1). This landslide produced a tsunami that damaged the villages on Stromboli and affected coastal zones around the southern Tyrrhenian Sea [Pino et al., 2004]. Following the landslide, the eruption was mostly characterized by effusive activity with lava flows extending from vents between 500 and 650 m above sea level. Simultaneous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 7 publications
1
24
0
Order By: Relevance
“… Barnet et al , 1997]. Similarly, a progressive increase in the number of Very Long Period events (VLP) has been recorded during March 2003 [ Ripepe et al , 2004].…”
Section: Discussionmentioning
confidence: 99%
“… Barnet et al , 1997]. Similarly, a progressive increase in the number of Very Long Period events (VLP) has been recorded during March 2003 [ Ripepe et al , 2004].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, infrasonic pressure was recorded for 74 of the 93 Type 2 NE-1 eruptions by University of Firenze microphones (Ripepe et al 2004, with results shown in Fig. 9.…”
Section: Origin Of Type 2a and 2b Stylesmentioning
confidence: 99%
“…Although the value of ground‐based (handheld or tripod‐mounted) thermal imaging and thermal infrared thermometers in volcanology has long been recognized [e.g., Decker and Peck , 1967; Shimozuru , 1971; Birnie , 1973], only recently has the routine use of ground‐based thermal measurements become widely reported. In recent years, ground‐based thermal infrared measurements of active volcanic features have been used to achieve the following: (1) recognize magma movements within the central conduits, detect the upward movement of shallow feeder dikes and track eruptive activity [ Calvari et al , 2003; Harris et al , 2003]; (2) measure the thermal and rheological properties of active basaltic lava flows, lava tubes and silicic (block) lava flows [ Flynn and Mouginis‐Mark , 1994; Hon et al , 1994; Harris et al , 2002; Kauahikaua et al , 2003; Wright and Flynn , 2003; Andronico et al , 2004]; (3) analyze the evolution of fumarole fields [ Harris and Maciejewski , 2000], active eruption plumes [ McGimsey et al , 1999; Dehn et al , 2002; Kaneko et al , 2002; Matsushima et al , 2003], strombolian activity and persistent degassing [ Harris et al , 1996; Ripepe et al , 2004]; (4) obtain effusion rate for active lava flows [ Harris et al , 2005]; (5) detect potential failure planes on recently formed cinder cones [ Calvari and Pinkerton , 2004] and fractures developing just before flank collapse at active volcanoes [ Bonaccorso et al , 2003]; and (6) analyze active lava lakes [ Flynn et al , 1993; Oppenheimer and Yirgu , 2002]. …”
Section: Introductionmentioning
confidence: 99%